Ethics in computing a concise module - Kizza, Joseph Migga (Switzerland Springer International Publishing, 2016)
"Raises thought-provoking questions regarding our rapidly-evolving computing technologies, highlighting the need for a strong ethical framework in our computer science education. Ethics in Computing offers a concise introduction to this topic, distilled from the more expansive Ethical and Social Issues in the Information Age. Features: introduces the philosophical framework for analyzing computer ethics; describes the impact of computer technology on issues of security, privacy and anonymity; examines intellectual property rights in the context of computing; discusses such issues as the digital divide, employee monitoring in the workplace, and health risks; reviews the history of computer crimes and the threat of cyberbullying; provides coverage of the ethics of AI, virtualization technologies, virtual reality, and the Internet; considers the social, moral and ethical challenges arising from social networks and mobile communication technologies; includes discussion questions and exercises"-- Provided by publisher.
Morality and the law -- Ethics and ethical analysis -- Ethics and the professions -- Anonymity, security, privacy, and civil liberties -- Intellectual property rights and computer technology -- Social context of computing -- Software issues: risks and liabilities -- Computer crimes -- Cyberbullying -- New frontiers for computer ethics: artificial intelligence, virtualization, and cyberspace -- Ethical, privacy, and security issues in the online social network ecosystem -- Elastic extension beyond the traditional computer network: mobile systems and intractable social, ethical, and security issues.
Includes bibliographical references and index.
Keywords: Computers -- Moral and ethical aspects